IMPLEMENTASI PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2015 TENTANG ITSBAT NIKAH TERPADU PERSPEKTIF MASLAHAH MURSALAH (Studi Pada Pengadilan Agama Kelas IIA. Manna) - Fajri, Aswadi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
This study  discusses  the implementation of the determination of Integrated  Marriage  of Religious Court  Class IIA Manna  in District Kedurang  South  Bengkulu  Regency.  the establishment of marriage  is a provision  of marriage  proven  by a religious court. The legal basis of marriage  isbat is the Compilation of Islamic Law contained in Article 7 paragraph (1) Com- pilation  of Islamic Law affirms that marriage  can only be proved  by the Marriage Certificate made  by the Officer of Marriage Recorders. This indicates  that marriages  that do not have  proof of registration  can be submitted to the establishment of mar- riage in religious courts accompanied by certain requirements. The purpose of the isbat marriage  is to get a new marriage  book through  the establishment of ratification in accordance with the Law No. 1 of 1974 without doing aqad  marriage  again. Among the reasons  for implementing the establishment of Integrated  Marriage is to provide  solutions for couples  whose marriages  are not recorded. The purpose of this study is to know the rule of law issued by the Supreme Court relating to the establishment of Integrated  Marriage and the application of Supreme Court Regulation  No. 1 Year 2015 By Manna  Religious Court. This type of research  is a type of field research  using qualitative  descriptive  approach. The research  data  is taken directly from the research location  and the data  is obtained by using interview method, observation and documentation method. After the data  collected to analyze the data collected in this study used analytical descriptive-analytic technique, which describes all the things that focus in this research. The results of this study indicate  that the Regulation  of the determination of Integrated  Marriage contained in Perma  No 1 Year 2015 which regulates the mechanism of implementation of an integrated determination session. As for the rule of law remains  based  on existing rules. Meanwhile,  the establishment of integrated marriage  is conducted by Manna  Religious Court in Kedurang  sub-district in accordance with Perma  No 1 year 2015.  Legal basis of the determination of Marriage Regula- tion Terhadi  namely  KHI Article 7 paragraph (1). While the judge’s consideration in deciding  the determination of Integrated Marriage is a problem.  With the establishment of marriage, the protection of the rights of each partner  because of their marriage has obtained legal recognition  and  provide  assurance of life, property  and  descent  which is the principle that must be kept in Islam (Ushulul Khomsah